2019
DOI: 10.1038/s41598-019-43636-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in molecular organization of type I collagen in tendon as probed by polarized SHG and Raman microspectroscopy

Abstract: Type I Collagen is one of the most abundant proteins of the extracellular matrix of the most organs. During chronological aging or in diseases, type I collagen undergoes biochemical and structural changes which can impact biomechanical and physiological properties of organs. In this study, we have investigated the age-related changes in the molecular organization of type I collagen in rat tails tendon using polarized Raman spectroscopy. Our results show that Amide I, amide III as well as the bands related to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…10a presents the primary structure of type I collagen showing the amino acid motif (Gly-X-Y), where X represents the proline (pro) and Y represents hydroxyproline (HyPro) respectively. [58][59][60] Fig. 10b ensures that the presence of hydrogen bonding between -CONHin the collagen brils of the IESM lattice structure.…”
Section: Mechanism Of the Proposed Sensor Arraymentioning
confidence: 97%
See 1 more Smart Citation
“…10a presents the primary structure of type I collagen showing the amino acid motif (Gly-X-Y), where X represents the proline (pro) and Y represents hydroxyproline (HyPro) respectively. [58][59][60] Fig. 10b ensures that the presence of hydrogen bonding between -CONHin the collagen brils of the IESM lattice structure.…”
Section: Mechanism Of the Proposed Sensor Arraymentioning
confidence: 97%
“…The change in the thickness of the IESM is predominant due to the porous nature of the micro-brils and proteins present in the IESM. 57,58 The cross-sectional SEM images in Fig. 9a and b show the comprehensive picture of the porous structure of the IESM.…”
Section: Mechanism Of the Proposed Sensor Arraymentioning
confidence: 99%
“…Chang et al have shown that in a 2D collagen coating model, an increase of type I collagen rigidity rendered NSCLC cells A549 more resistant to erlotinib (8). Previous studies from our group have shown that age-related modifications of type I collagen were linked to an increase of its rigidity (17,18), and could modulate tumor cells behavior when used in a more physiological 3D model. Since lung carcinoma cells are confronted to a collagen rich microenvironment, we decided to investigate the effect of collagen aging on the toxicity of erlotinib on A549 and BZR cells by determining the IC 50 of erlotinib in adult and old collagen, for both cell lines.…”
Section: Collagen Aging Promotes Lung Cancer Cells Resistance To Erlomentioning
confidence: 90%
“…Here, human and bovine bone generated stronger background fluorescence than synthetic HAp. Demineralised bovine bone, despite exhibiting the most intense background fluorescence, displayed many of the characteristic spectral features associated with type-I collagen 13,25,26 , both before and after baseline subtraction.…”
Section: Discussionmentioning
confidence: 99%